The future and the progress of innovation in the healthcare system - Nurhidayah, Nurhidayah; Seaharattanapatum, Bootsakon (Innovation in Health for Society, 2021)
Innovation in nursing is essential to develop and increase the quality of care in hospital and community settings. At this present, innovation should be used to assess, diagnose, plan, implement and evaluate as mentioned in the nursing process. In addition, it may be used for producing valid information, protecting nurses, preventing disease, and offering patient care. For this reason, clinical nurses must engage in innovative technology in daily practice to improve the outcome and reduce the cost of care. A rise in both interest in and demand for novel approaches to healthcare delivery can be attributed to the COVID-19 epidemic. To maintain their relevance and be competitive in the market, organizations have difficulty striking a balance between the aims of day-to-day operations and innovation. Innovation is essential not just to the prosperity and continued existence of businesses but also to the health and happiness of the faculty, staff, and customers that those businesses serve—the review aimed to evaluate the future and progress of innovation in healthcare. Keywords: Innovation; nurses’ perspective; healthcare; nursing care; patient care